Reductive Precipitation of Heavy Metals in Soil and Groundwater using Abiotic and Biologically Mediated Processes - Molin, Josephine; Seech, Alan; Shoiti Matsura, Afonso (Águas Subterrâneas, 2019)
EHC® Metals is a remediation product for immobilization of metals composed of organic carbon, micro-scale zero-valent iron (ZVI) and sulfate. Following placement of EHC Metals substrate into the saturated zone, a number of chemical and microbiological processes combine to create strongly reducing conditions under which a number of heavy metals are sequestered via reductive precipitation as scarcely soluble metal-sulfides and via adsorption onto secondary ZVI corrosion products. These reactions are microbially mediated, in part relying on microbial organic carbon fermentation and on the reduction of sulfate by sulfate-reducing bacteria. At very high concentrations, heavy metals can be acutely toxic to microorganisms and approaches that rely on microbial processes may not function well if microbial activity is significantly slowed or inhibited. MetaFix™ reagents represent an entirely new family of reagents for treatment of heavy metals, composed of mixtures of reducing agents (ZVI, iron sulfides), processed reactive minerals (iron oxides, iron oxyhydroxides), pH modifiers, silicates, and catalysts. This new approach is abiotic and therefore insensitive to toxicity. Performance data will be presented, including an evaluation of both EHC Metals and Metafix for a site in Brazil.